Identification of Snowdrop Virus Y Occurred on Narcissus spp. in Korea - Minseok Kim; Minhui Kim; Sangmin Bak; Hak ju Kim; Hong-Kyu Lee; Jean Geung Min; Taegun Lim; Seungbin Baek; Minjoo Yang; Dong-Joo Min; Jin-Sung Hong; Hee-Seong Byun; et al. (Research in Plant Disease)
Metatranscriptome analysis and reverse transcription polymerase chain reaction diagnostics were conducted to investigate viral disease in 75 Narcissus samples, resulting in the detection of snowdrop virus Y (SVY). The complete genome sequence of the SVY isolate SA66 was 10,560 nt in length, and sequence analysis revealed a typical genome structure for Potyvirus. Electron microscopy revealed filamentous rod particles approximately 800 nm long in the infected samples. In the bioassay involving 19 test plants, no SVY infection was confirmed. The coat protein sequences of 10 SVY isolates from various samples were determined, showing nucleotide identities of 99.3-99.8% and amino acid identities of 98.9-99.6% when compared with three previously reported isolates. The complete genome sequence shared 99.6% nucleotide identity and 99.7% amino acid identity with the reported isolate. SVY was detected in 10 of the collected samples, specifically showing partial detection in all four cultivars from the Sinan region, while it was not detected in the other three regions. This study is the first report of SVY in Korea and is expected to contribute to the quarantine of Narcissus bulbs and to the production of virus-free bulbs.